2016
DOI: 10.1111/1750-3841.13271
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamomum camphora Seed Kernel Oil Ameliorates Oxidative Stress and Inflammation in Diet‐Induced Obese Rats

Abstract: Cinnamomum camphora seed kernel oil (CCSKO) was found to reduce body fat deposition and improve blood lipid in both healthy and obese rats. The study was aimed to investigate the antioxidative stress and anti-inflammatory effects of CCSKO in high-fat-diet-induced obese rats. The obese rats were treated with CCSKO, lard, and soybean oil, respectively, for 12 wk. The level of total antioxidant capacity (T-AOC), activities of superoxide dismutase (SOD), glutathione peroxidase, and catalase, and levels of malondia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…that Cinnamomum camphora seed kernel oil treatment significantly increased the activities of SOD and GSH‐PX in serum in HFD‐induced obese rats when compared to lard and soybean oil groups. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…that Cinnamomum camphora seed kernel oil treatment significantly increased the activities of SOD and GSH‐PX in serum in HFD‐induced obese rats when compared to lard and soybean oil groups. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress occurs when there is an imbalance between the production of reactive metabolites and the activity of antioxidant enzymes. Many studies have shown that oxidative stress is significantly increased in obese patients and animals and causes direct or indirect damage to various organs[31,32]. MDA is a toxic decomposition product of lipid peroxidation degradation, and the MDA content can reflect the degree of oxidative stress and cell damage[33].…”
Section: Discussionmentioning
confidence: 99%
“…According to the presented findings, it can be speculated that the effects might be caused through inhibiting the expression of proinflammatory genes, such as those for cytokines and cytotoxic-moleculegenerating enzymes, including inducible nitric oxide synthase and cyclooxygenase, via affecting the nuclear factor kappa B pathway. Furthermore, it has been reported that CCEO extracted from seeds could reduce the levels of inflammatory markers (tumor necrosis factor-α, interleukin-6 and P65), probably through upregulating peroxisome proliferator-activated receptor [56]. Moreover, another study reported that 80% ethanol extract of C. camphora leaves exhibits anti-inflammatory effects by phosphorylation of signal transducer, activator of transcription 1 and extracellular signal-regulated kinase 1/2 [57].…”
Section: Anti-inflammatory Actionmentioning
confidence: 98%
“…CCEO has a certain antioxidant capacity, which increases with essential oil concentration [62]. It has been reported that CCEO can reduce the number of reactive oxygenfree radicals via improving the activities of antioxidant enzymes, so as to have an antioxidant effect [56]. In addition, a high concentration of C. osmophloeum Kanehira extract has been proven to have an obvious free-radical scavenging capability [63].…”
Section: Antioxidant Activitymentioning
confidence: 99%